2022
DOI: 10.1371/journal.pone.0268599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early mobilization combined with early nutrition on acquired weakness in critically ill patients (EMAS): A dual-center, randomized controlled trial

Abstract: Aim The study aimed to investigate the effect of early mobilization combined with early nutrition (EMN) on intensive care unit-acquired weakness (ICU-AW) in intensive care unit (ICU) settings compared with early mobilization (EM) or routine care. Methods A prospective, dual-center, randomized controlled trial was conducted. The control group underwent standard care without a pre-established routine for mobilization and nutrition. The EM group underwent early, individualized, progressive mobilization within 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…It makes the establishment of causal relations in these studies questionable. This was consistent with other studies that showed comparable associations between protein delivery and mortality, as well as an effect on functional outcomes and muscle mass 17,82–84 . In addition, other studies found that publication bias might be a concern in smaller studies that reported less loss of muscle mass in patients receiving more protein 69 …”
Section: Discussionsupporting
confidence: 90%
“…It makes the establishment of causal relations in these studies questionable. This was consistent with other studies that showed comparable associations between protein delivery and mortality, as well as an effect on functional outcomes and muscle mass 17,82–84 . In addition, other studies found that publication bias might be a concern in smaller studies that reported less loss of muscle mass in patients receiving more protein 69 …”
Section: Discussionsupporting
confidence: 90%
“…Four of these studies were randomized controlled trials [18][19][20][21], one was a historical control study [22], and one was a pre/post cohort study in a coronavirus disease 2019 (COVID-19) population [23]. Four studies were conducted in Asia [19][20][21][22], and one was conducted in Europe [23], and one in South America [18]. The main type of nutritional interventions included overall nutritional intake with delivery of both calories and proteins.…”
Section: The Current Challengementioning
confidence: 99%
“…Six studies (Table 1) were identified that combined both interventions. Four of these studies were randomized controlled trials [18][19][20][21], one was a historical control study [22], and one was a pre/post cohort study in a coronavirus disease 2019 (COVID-19) population [23]. Four studies were conducted in Asia [19][20][21][22], and one was conducted in Europe [23], and one in South America [18].…”
Section: The Current Challengementioning
confidence: 99%
See 2 more Smart Citations